Prosecuting The House of God: The Irony of Rights to Freedom of Worship for Dhimmi Minority in Indonesia - Yusuf Hanafi; M. Alifudin Ikhsan (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2019)
The freedom to embrace a religion and belief and worshiping are the rights of each citizen protected by the constitution, including the Dhimmi minority, as the state authorities have issued a Joint Regulation Number 8 and 9 of 2006 on the Guideline of Empowering the Forum of Religious Harmony and Constructing Worship House. Ironically, instead of giving the sense of justice for all society elements, regulations are deemed to limit the activity of worshiping of dhimmi minority. In realizing the equal rights to worship and constructing the house of worship for the Dhimmi minority, the Regulation should be submitted to the Supreme Court to undergo juridical review. The suggestions utilized to review several articles are considered as discriminating us the society's actualization on the government’s product of law. This piece of writing explored the problems of constructing the house of worshiping the context of the rights to worship for dhimmi minority through the Quran's perspective. The conception of the Qur'an generated is reflected in the idea of the jurisprudence of human rights, which strives for establishing the equality of rights to worship for citizens. The jurisprudence of human rights is expected to raise social awareness to appreciate and respect the worshiping activities of dhimmi minority, reducing the retention of inter-religious violence, and creating a harmonious life based on the principles of Islamic law in Maqasid al-Syariah.Kebebasan memeluk agama dan keyakinan serta menjalankan peribadatannya merupakan hak asasi setiap warga negara yang dilindungi oleh konstitusi, termasuk bagi minoritas dhimmi. Pemerintah sebagai pemegang kekuasaan negara telah mengeluarkan Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri Nomor 8 dan 9 Tahun 2006 tentang Pedoman Pemberdayaan Forum Kerukunan Umat Beragama dan Pendirian Rumah Ibadah. Ironisnya, Peraturan yang sejatinya memberi rasa keadilan bagi seluruh elemen masyarakat, justru terkesan membatasi aktivitas peribadatan minoritas dhimmi. Untuk mewujudkan kesamaan hak beribadah dan mendirikan rumah ibadah bagi minoritas dhimmi, Peraturan tersebut perlu diajukan ke meja Mahkamah Agung guna menjalani judicial review. Usulan untuk meninjau kembali beberapa pasal yang dianggap diskriminasi tersebut merupakan wujud pengawasan masyarakat terhadap produk hukum Pemerintah. Tulisan ini mengkaji problematika pendirian rumah ibadah dalam konteks hak beribadah minoritas dhimmi melalui perspektif Alquran. Konsepsi Alquran yang dihasilkan dituangkan dalam gagasan fikih HAM yang berupaya untuk membangun kesetaraan hak beribadah bagi warga negara. Fikih HAM diharapkan mampu membentuk kesadaran masyarakat untuk menghargai dan menghormati aktivitas peribadatan minoritas dhimmi, mengurangi retensi kekerasan antar umat beragama, dan menciptakan kehidupan yang harmonis berdasarkan prinsip-prinsip syariat Islam dalam Maqasid al-Syariah.